(untitled) (Journal of Pharma Insights and Research, 2024)
This case report underscores the imperative for continuous research, heightened awareness, and collaborative efforts among healthcare professionals to advance the understanding and management of cutaneous tuberculosis. Cutaneous tuberculosis, a rare extrapulmonary manifestation, necessitates a comprehensive diagnostic approach, integrating clinical, microbiological, and histopathological evidence for accurate identification. Untreated tuberculosis (TB) can be lethal, emphasizing the significance of timely intervention. The initiation of Anti-Tubercular Therapy (ATT) is pivotal for addressing cutaneous tuberculosis, involving rifampicin, ethambutol, pyrazinamide, and isoniazid. This form of TB manifests as a primary skin infection and exhibits varying prevalence patterns in industrialized and less affluent nations. In industrialized settings, it is often associated with individuals undergoing immunosuppressive therapy, battling cancer, subject to chronic corticosteroid therapy, or experiencing malnourishment. Conversely, cutaneous tuberculosis is more prevalent in the general healthy population in less affluent regions. The distinct characteristics of cutaneous tuberculosis, such as granulomatous inflammation and variable necrosis, are discerned through diverse morphological presentations, specific staining techniques, culture, or polymerase chain reaction (PCR) tests. Approximately 1-1.5% of extrapulmonary tuberculosis cases can be attributed to cutaneous tuberculosis, including scrofuloderma, lupus vulgaris, orificial TB, miliary tuberculosis, metastatic tuberculosis abscess, and the majority of papulonecrotic tuberculid cases. This case underscores the variability in symptom manifestation, contributing to the broader understanding of tuberculosis disease progression. This emphasizes the need for comprehensive diagnostic approaches and tailored treatment strategies to optimize patient outcomes